1973
DOI: 10.1139/v73-366
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of 1,1′-Carbonyl- and 1,1′-Sulfinyl-dipyrazoles and their Reactions with Carbonyl Compounds

Abstract: The compounds 1,1′-carbonylbis(3-methylpyrazole) (1), 1,1′-carbonylbis(3,5-dimethylpyrazole) (2), and 1,1′-sulfinyldipyrazole (3) have been prepared. They react with aldehydes and ketones in the presence of metal ion catalysts to form 1,1′-alkylidenedipyrazoles together with carbon dioxide, from 1 and 2, or sulfur dioxide, from 3. Tetrapyrazol-1-ylmethane results from the pyrolysis at 200° of 1,1′-carbonyldipyrazole in the presence of cobalt(II) chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

1973
1973
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 1 publication
3
30
0
1
Order By: Relevance
“…For the preparation of 2 a to 2 c, a synthetic protocol based on that of Peterson et al [41][42][43] was employed. Treatment of aldehydes 1 a to 1 c (Scheme 1) with bis(pyrazol-1-yl)methanone (1.2 equiv) in the presence of a catalytic amount of anhydrous CoCl 2 gave 2 a to 2 c in yields of between 23 and 36 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the preparation of 2 a to 2 c, a synthetic protocol based on that of Peterson et al [41][42][43] was employed. Treatment of aldehydes 1 a to 1 c (Scheme 1) with bis(pyrazol-1-yl)methanone (1.2 equiv) in the presence of a catalytic amount of anhydrous CoCl 2 gave 2 a to 2 c in yields of between 23 and 36 %.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 1 a and 8 are commercially available. Compounds 1 b, [54] 1 c, [54] 3 [27] and bis(pyrazol-1-yl)methanone [42] were synthesised according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Seminal works by Peterson and co-workers [19] showed that the reaction of 1,1¢-carbonyldipyrazoles with carbonyl compounds (e.g., aldehydes or ketones) catalyzed by CoCl 2 (Scheme 4) readily yields substituted 1-R¢-bis(pyrazolyl)methanes. The proposed mechanism involves coordination of the 2-and 2¢-nitrogens of the 1,1¢-carbonyldipyrazole to Co 2+ followed by the heterolytic cleavage of the carbonyl-nitrogen bond (Scheme 5) and formation of the carbamate intermediate by insertion of the aldehyde or ketone.…”
Section: Synthesis Of the Ligandsmentioning
confidence: 99%
“…Reaction of the titanium complex 11 with one equiv of [Ph 3 (19). Ring opening reaction of THF was not observed with 15 because of the less nucleophilic character of the borate anion and/or lower electrophilicity of titanium.…”
Section: Reactivity Of the Heteroscopionates 11-13mentioning
confidence: 99%
“…Our recent investigations showed that functionalized bis(pyrazol-1-yl)methanes by the organic groups on the methine carbon atom provided unusual reactivity [20,21,29,30]. For instance, the reaction of Ph 3 SnCH(3,5-Me 2 Pz) 2 (Pz ¼ pyrazol-1-yl) with W( CO) 5 THF resulted in the oxidative addition reaction of the Sn-C sp3 bond to the tungsten(0) atom to yield novel four-membered metallacyclic complexes [30], while the analogous reaction of Ph 2 (I)SnCH(3,5-Me 2 Pz) 2 led to the oxidative addition of the relatively electrophilic SneI bond to the tungsten(0) atom to form five-membered metallacyclic complexes [31]. These results encourage us to explore the relative reactivity of other bis(pyrazol-1-yl)methanes substituted on the bridgehead carbon atom with carbonyl tungsten derivatives.…”
Section: Introductionmentioning
confidence: 99%